RISK ANALYSIS AND MODELING OF INVESTMENT PROJECT IMPLEMENTATION SCENARIOS - Ashurova Oltin Yuldashevna; Khabibkulova Shahzoda Umidovna; Ravshanova Vazira Sukhrobovna (Antis Publisher, 2024)
Investment decisions, decisions on initiating investment projects that are significant for the company should be made on the basis of a thorough analysis of the associated risks. Successful implementation of the adopted investment projects is also impossible without thoughtful and reasonable risk management, the impact of which threatens the achievement of the goals of any project. In addition, in conditions of economic instability, it is becoming increasingly difficult to attract funds for investment, which necessitates a more thorough justification of projects, including in the field of risk assessment and management. The course examines the main processes and tools for managing project risks, with an emphasis on their quantitative assessment, including using specialized software.